On the crossing number of some complete multipartite graphs - Ho, Pak Tung (Utilitas Mathematica, 2009)
In this paper, we compute the crossing number of the complete multipartite graphs K 1,1,1,1,n, K 1,2,2,n, K 1,1,1,2,n and K 1,4,n..